The impact of health communication through sports social media on adolescents’ sport participation attitudes: a moderated mediation model - Jiawei Chen; Mengfen Liu; Jinmei Hu; Jianhua Zhang (Scientific Reports)
Abstract Sport Participation Attitudes are important factors influencing individuals’ physical health. From the perspective of the social-ecological model, this study explores the relationship and mechanisms between Health Communication through Sports Social Media(HCTSSM) and adolescents’ sport participation attitudes through the construction and testing of a moderated mediation model. A cross-sectional design was employed to examine the mediating roles of social support and self-efficacy in the impact of Health Communication through Sports Social Media on Sport Participation Attitudes. Data were collected from 920 adolescents using the Health Communication through Sports Social Media, Sports Attitude, Social Support, and the Self-Efficacy Scales. The results showed that: (1) HCTSSM has a significant positive impact on adolescents’ Attitudes Towards Sports; (2) self-efficacy plays a mediating role in the relationship between HCTSSM and adolescents’ Attitudes Towards Sports; (3) social support moderates the latter half of the mediation process, where HCTSSM influences adolescents’ participation attitudes through self-efficacy. Based on the findings, it is recommended that sports social media platforms prioritize enhancing users’ social support and self-efficacy. Specifically, the selection and design of health communication content should focus on experience-sharing and health belief-oriented materials. This approach is likely to be more effective in fostering positive attitudes toward sports participation.